Science in Libraries - A. Yu. Samarin; E. A. Pleshkevich; N. K. Lelikova; M. Ya. Dvorkina; G. V. Varganova; O. I. Lavrik (Библиосфера)
The discussion reflects the points of view of doctors of sciences from the Russian State Library, the Russian National Library, the Saint-Peterburg State Institute of Culture and the State Public Scientific and Technical Library of the Siberian Branch of the Russian Academy of Sciences (SPSTL SB RAS), voiced on March 16, 2022 at the round table “Science in Libraries”. The round table was held within the framework of the international conference “Libway” held by the SPSTL SB RAS. The participants of the discussion answered the following questions: general assessment of the state of domestic library science, book science, bibliography; key areas of library science, book science and bibliography in the second decade of the 21st Century; problems of scientific personnel training; the place of library science and the prospects for its development within the new Nomenclature of scientific specialties. The discussion made it possible to single out the following problems: the importance of solving practice-oriented problems of library science and bibliography, and only then their theoretical analysis and generalization; work in the library field of specialists from other industries with a poor understanding of librarianship and bibliography issues; lack of educational and methodological materials for graduate students and their supervisors; a very small number of state-funded places in graduate school and the lack of material incentives to attract specialists to scientific research. In a general assessment of the state of the disciplines of the documentary and communication cycle, opinions differed – from an optimistic view of the future of these disciplines to a pessimistic one due to the presence of numerous internal problems. The necessity of collaboration is stressed. All participants expressed their deepest satisfaction with the inclusion of library, bibliography and book sciences in the new Nomenclature of scientific specialties and the emergence of a new specialty passport.